2019
DOI: 10.1182/blood-2019-122706
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Treatment Trends in Relapsed/Refractory Multiple Myeloma (RRMM) in Europe from 2016 to 2018: Analysis of a Multi-National Survey

Abstract: Background Recently, treatment options for RRMM have increased substantially with multiple approvals of novel agents/combination, making the treatment algorithm increasingly complex, with changes driven chiefly by access to novel agents/regimens. Furthermore, patient (pt) and disease characteristics have a profound impact on treatment decisions. To understand the impact of recently approved novel regimens on real-world (RW) treatment patterns, we conducted a multi-national survey to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Although in both Europe and the USA bortezomib is the most commonly used proteasome inhibitor in the first-line setting, and in combination with novel agents in second and later lines [ 36 , 37 ], in our study, it was prescribed mainly in combination with daratumumab in second and third lines (9% and 11%, respectively). Overall, there are clear differences in treatment practice between countries [ 20 , 21 , 37 39 ], with no standard of care for patients with RRMM in later lines of treatment, and treatment algorithms evolving over time [ 21 , 36 , 37 , 39 ]. The changing landscape and treatment practice differences between countries are related to the introduction of various novel therapies over recent years, as the timings of regulatory approvals and reimbursement differ between Europe and the USA, and the time taken for such agents to become available after approval varies across Europe [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in both Europe and the USA bortezomib is the most commonly used proteasome inhibitor in the first-line setting, and in combination with novel agents in second and later lines [ 36 , 37 ], in our study, it was prescribed mainly in combination with daratumumab in second and third lines (9% and 11%, respectively). Overall, there are clear differences in treatment practice between countries [ 20 , 21 , 37 39 ], with no standard of care for patients with RRMM in later lines of treatment, and treatment algorithms evolving over time [ 21 , 36 , 37 , 39 ]. The changing landscape and treatment practice differences between countries are related to the introduction of various novel therapies over recent years, as the timings of regulatory approvals and reimbursement differ between Europe and the USA, and the time taken for such agents to become available after approval varies across Europe [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The changing landscape and treatment practice differences between countries are related to the introduction of various novel therapies over recent years, as the timings of regulatory approvals and reimbursement differ between Europe and the USA, and the time taken for such agents to become available after approval varies across Europe [ 36 ]. Of note, in Germany, novel treatments are available/reimbursed immediately after regulatory approval, meaning that these agents are often available earlier in Germany than elsewhere [ 36 , 39 ]. Data from the present German study, therefore, provide useful insights into the uptake of novel agents in this rapidly changing treatment landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Although there continues to be no standard of care for RRMM in Europe [32], recent studies show that lenalidomide is often the most common treatment, and PI-based regimens, including triplets, are increasingly being prescribed [21,33]. Practice patterns in France differ from the rest of Europe, and only a few studies have reported on recent treatment patterns in RRMM that are specific to the French population [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The European Society for Medical Oncology (ESMO) guidelines mainly recommend using these novel agents in doublet and triplet combination regimens that include a corticosteroid (dexamethasone or prednisone) [4,18]. However, it remains unclear to what extent guideline recommendations translate into clinical practice [17], and there is relatively little current evidence on real-world treatment patterns for RRMM in France [19,20], Europe [1,[21][22][23][24], or indeed elsewhere [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, patient outcomes with cilta-cel, as observed in CARTITUDE-1, were compared with outcomes from similar patients treated with RWCP, as observed in Therapie Monitor in Germany. Therapie Monitor provides a representative sample of patients from German routine clinical practice and has excellent variable coverage, ensuring reliable comparisons [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. This is further illustrated by the observed median OS and TTNT in Therapie Monitor of 9.89 and 6.21 months, respectively, consistent with outcomes in other sources and geographies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%